The Relationship Between Nurses' Therapeutic Communication and Patient Satisfaction Treated in the Mawar and Melati Treatment Rooms at Mamuju District Hospital - Yuliana D; Suaib; Nur Fadilah A; Rismalasari Dewi; Nur, Akbar (Journal Kiara : Nursing and Midwifery, 2025)
Patient satisfaction is the main indicator in assessing the quality of health services in hospitals. One factor that plays a role in patient satisfaction is therapeutic communication carried out by nurses. Effective therapeutic communication can build a relationship of mutual trust between nurses and patients, increasing patient comfort and satisfaction. This study aims to determine the relationship between nurse therapeutic communication and patient satisfaction treated in the Mawar and Melati rooms at the Mamuju District Hospital. This study used a cross-sectional design with a simple random sampling technique. The study sample consisted of inpatients who met the inclusion criteria. Data were collected using a questionnaire that measured the level of nurse therapeutic communication and patient satisfaction. Data analysis was performed using the Chi-Square test. The results of this study indicate that the p-value is 0.440 (>0.05), which means that there is no significant relationship between the therapeutic communication of nurses at the Mamuju District Hospital and the level of patient satisfaction at the Mamuju District Hospital. This indicates that other factors, such as health facilities, responsiveness of services, and patient conditions, may have a greater influence on patient satisfaction.